Answer
The zeros of the function \( f(x) = 2x^2 - 23.6x + 67 \) are approximately \( x \approx 4.755 \) and \( x \approx 7.045 \).
Solution
Solve the quadratic equation by following steps:
- step0: Solve using the quadratic formula:
\(2x^{2}-23.6x+67=0\)
- step1: Convert the decimal into a fraction:
\(2x^{2}-\frac{118}{5}x+67=0\)
- step2: Multiply both sides:
\(5\left(2x^{2}-\frac{118}{5}x+67\right)=5\times 0\)
- step3: Calculate:
\(10x^{2}-118x+335=0\)
- step4: Solve using the quadratic formula:
\(x=\frac{118\pm \sqrt{\left(-118\right)^{2}-4\times 10\times 335}}{2\times 10}\)
- step5: Simplify the expression:
\(x=\frac{118\pm \sqrt{\left(-118\right)^{2}-4\times 10\times 335}}{20}\)
- step6: Simplify the expression:
\(x=\frac{118\pm \sqrt{524}}{20}\)
- step7: Simplify the expression:
\(x=\frac{118\pm 2\sqrt{131}}{20}\)
- step8: Separate into possible cases:
\(\begin{align}&x=\frac{118+2\sqrt{131}}{20}\\&x=\frac{118-2\sqrt{131}}{20}\end{align}\)
- step9: Simplify the expression:
\(\begin{align}&x=\frac{59+\sqrt{131}}{10}\\&x=\frac{118-2\sqrt{131}}{20}\end{align}\)
- step10: Simplify the expression:
\(\begin{align}&x=\frac{59+\sqrt{131}}{10}\\&x=\frac{59-\sqrt{131}}{10}\end{align}\)
- step11: Rewrite:
\(x_{1}=\frac{59-\sqrt{131}}{10},x_{2}=\frac{59+\sqrt{131}}{10}\)
Calculate or simplify the expression \( (59+\sqrt(131))/10 \).
Calculate the value by following steps:
- step0: Calculate:
\(\frac{\left(59+\sqrt{131}\right)}{10}\)
- step1: Remove the parentheses:
\(\frac{59+\sqrt{131}}{10}\)
Calculate or simplify the expression \( (59-\sqrt(131))/10 \).
Calculate the value by following steps:
- step0: Calculate:
\(\frac{\left(59-\sqrt{131}\right)}{10}\)
- step1: Remove the parentheses:
\(\frac{59-\sqrt{131}}{10}\)
To find the zeros of the function \( f(x) = 2x^2 - 23.6x + 67 \), we need to solve the equation \( 2x^2 - 23.6x + 67 = 0 \).
### Step 1: Identify the coefficients
The coefficients of the quadratic equation are:
- \( a = 2 \)
- \( b = -23.6 \)
- \( c = 67 \)
### Step 2: Use the quadratic formula
The quadratic formula to find the roots (zeros) of the equation \( ax^2 + bx + c = 0 \) is given by:
\[
x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}
\]
### Step 3: Calculate the discriminant
First, we calculate the discriminant \( D = b^2 - 4ac \):
\[
D = (-23.6)^2 - 4 \cdot 2 \cdot 67
\]
Calculating this gives:
\[
D = 556.96 - 536 = 20.96
\]
### Step 4: Calculate the zeros
Now we can find the zeros using the quadratic formula:
\[
x_{1} = \frac{23.6 - \sqrt{20.96}}{4}
\]
\[
x_{2} = \frac{23.6 + \sqrt{20.96}}{4}
\]
### Step 5: Evaluate the zeros
Calculating these values gives:
- For \( x_{1} \):
\[
x_{1} \approx 4.755
\]
- For \( x_{2} \):
\[
x_{2} \approx 7.045
\]
### Final Answer
The zeros of the function \( f(x) = 2x^2 - 23.6x + 67 \) are approximately:
- \( x \approx 4.755 \)
- \( x \approx 7.045 \)
You can submit these values as your answer.
Reviewed and approved by the UpStudy tutoring team
Explain
Simplify this solution